Determinantes ecológicos de la competencia sexual en Belostomatinae. Consideraciones sobre una población de Belostoma oxyurum (Dufour) (Hemiptera, Belostomatidae) - Snack, J. A.; Domizi, Eduardo A.; Estevez, Ana L.; Spinelli, Gustavo R. (Ecosur, 2025)
Male’s Belostomatinae parental solicitude of incubating eggs as well as general ten- dencies and temporal changes in the sex ratio, are here referred to a Belostoma oxyurum population, in order to study their effects on female’s competition. Dorsal incubation space, which acts as a substrate, and obviously as a resourse, is asumed to be a limited requisite for gravid females during the reproductive seasons, according to its relative and absolute shortage. Some conclusive evidences are given from an annual sampling programme developed in “Laguna Los Talas" (Province of Buenos Aires, Argentine) from January 6 to December 27, 1978. Furthermore, preliminary observations carried on under experimental conditions allowed us to support our field experience, in order to prove the existence of intrasexual and intersexual selection as a mean to promote the temporary sexual unbalance observed in nature.